COPD Exacerbations, Costs, and Health Care Resource Utilization Before and After Initiation of Fluticasone Furoate/Umeclidinium/Vilanterol in Routine Care in the USA - Hanania NA; Bunner SH; Bengtson LGS; Ismaila AS; Bogart M (International Journal of COPD, 2023)
Nicola A Hanania,1 Scott H Bunner,2 Lindsay GS Bengtson,2 Afisi S Ismaila,3,4 Michael Bogart5 1Section of Pulmonary and Critical Care Medicine, Baylor College of Medicine, Houston, TX, USA; 2Optum, Eden Prairie, MN, USA; 3Value Evidence and Outcomes, GSK, Collegeville, PA, USA; 4Department of Health Research Methods, Evidence and Impact, McMaster University, Hamilton, ON, Canada; 5US Value Evidence & Outcomes, GSK, Research Triangle Park, NC, USACorrespondence: Afisi S Ismaila, Value Evidence and Outcomes, GSK, 1250 S. Collegeville Road, Collegeville, PA, 19426-0989, USA, Tel +1 919-3158229, Email afisi.s.ismaila@gsk.comPurpose: To examine the impact of initiating fluticasone furoate/umeclidinium/vilanterol (FF/UMEC/VI) in a single device on chronic obstructive pulmonary disease (COPD) exacerbations, COPD exacerbation-related costs, and all-cause and COPD-related healthcare resource utilization (HCRU) and costs in patients with COPD.Methods: Retrospective database analysis of patients with COPD aged ≥ 40 years who initiated FF/UMEC/VI between September 1, 2017, and December 31, 2018 (index date: first pharmacy claim for FF/UMEC/VI), following evidence of multiple-inhaler triple therapy (MITT) (≥ 30 consecutive days) in the year prior to index. COPD exacerbations, COPD exacerbation-related costs, and all-cause and COPD-related HCRU and costs were compared between the baseline period (12 months prior to and including index) and follow-up period (12 months following index).Results: Data from 912 patients (mean [SD] age: 71.2 [8.1], 51.2% female) were included in the analyses. Among the overall cohort, mean count of total COPD exacerbations (moderate or severe) per patient was statistically significantly lower in the follow-up period compared to baseline (1.2 vs 1.4, p=0.001). The proportion of patients with ≥ 1 COPD exacerbation (moderate or severe) was also statistically significantly lower in the follow-up period compared to baseline (56.4% vs 62.4%, p=0.001). All-cause and COPD-related HCRU were similar during follow-up compared to baseline, although the proportion of patients with COPD-related ambulatory visits was lower during follow-up (p< 0.001). COPD-related office visit costs, emergency room visit costs, and pharmacy costs were statistically significantly lower during follow-up compared to baseline (p< 0.001; p=0.019; p< 0.001, respectively).Conclusion: In a real-world setting, patients on MITT who subsequently initiated FF/UMEC/VI in a single device had significant reductions in the rate of COPD exacerbations (moderate or severe). Switching to FF/UMEC/VI also resulted in improvements in some HCRU and cost outcomes. These data support the use of FF/UMEC/VI among patients at high risk of exacerbation to reduce future risk and improve outcomes.Keywords: chronic obstructive pulmonary disease, exacerbations, healthcare utilization, multiple-inhaler triple therapy, FF/UMEC/VI, single-inhaler triple therapy